A methods engineering study on RM Corporation - Garcia, Maeleen (College of Engineering, 2001)
RM Corporation, based in Lipa City, Batangas manufactures hog and poultry feeds. Methods study is done on plant visits employing various tools in the documentation and analysis of the company operations. Using Streamline Diagnosis Diagram, the group identified four problems : inefficient plant layout, inefficient scheduling, lack of detailed job description, and no specifications of standard times. Alternatives are presented for each of the aforementioned problems. Two alternatives are proposed for the problem of inefficient plant layout. The first one includes the transfer of the expensive raw materials (ERMS) and the micro mixer room to the back of the plant. In the second alternative, the machines will be relocated in addition to the changes of the first alternative. For the problem of inefficient scheduling, four alternatives are proposed which includes training of management, hiring consultants and creating the new position of Assistant Production Manager (APM). Each of the proposals are evaluated using the Kepner-Tregoe approach to decision analysis. Moreover, the consequences are weighed through risk assessment. From the evaluation stage, the most expedient alternative is chosen. For the problem of inefficient plant layout, inefficient scheduling problem, and lack of detailed job description, the first, fourth and second alternatives are chosen respectively. The second alternative is chosen for lack of standard times. The group also came up with an implementation plan which will guide the company in carrying out the various changes brought about by the alternatives. Still, it is up to the company if the changes proposed will be applied.